2016
DOI: 10.1002/jmv.24681
|View full text |Cite
|
Sign up to set email alerts
|

The FAS‐670 AA genotype is associated with high proviral load in peruvian HAM/TSP patients

Abstract: Human T-lymphotropic virus 1 (HTLV-1) is the etiologic agent of the HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Apoptosis is a mechanism of defense elicited by many triggers, including cross-linking of the FAS receptor expressed in viruses-infected cells, and the ligand FASL presented by T-cytotoxic cells. As HAM/TSP has been associated with high levels of proviral load (PVL), we hypothesized that certain genotypes of single-nucleotide polymorphisms (SNPs) associated with a decreased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Recently, FAS −670 AA genotype was associated with high proviral load as compared to FAS −670 GG in HAM patients [70]. This result is in agreement with our study, where the genotype FAS −670AA was more frequent among HAM patients as compared to the asymptomatic individuals [69], suggesting that individuals carrying this genotype have a greater chance and a higher susceptibility to progress to overt clinical disease.…”
Section: Htlv-1 Infected Subjects’ Immunogenetic Profilesupporting
confidence: 92%
“…Recently, FAS −670 AA genotype was associated with high proviral load as compared to FAS −670 GG in HAM patients [70]. This result is in agreement with our study, where the genotype FAS −670AA was more frequent among HAM patients as compared to the asymptomatic individuals [69], suggesting that individuals carrying this genotype have a greater chance and a higher susceptibility to progress to overt clinical disease.…”
Section: Htlv-1 Infected Subjects’ Immunogenetic Profilesupporting
confidence: 92%
“…Recently, one study reported an association between polymorphisms in the TREX and SAMHD1 genes and increased proviral load of HTLV-1 among people with HAM [ 92 , 93 ]; similar results had also been described previously [ 88 , 94 , 95 , 96 ]. These data reinforce the need for further epidemiological genetic studies involving a larger number of people infected with HTLV-1 to better understand the effect of these markers on the pathogenesis and natural history of HAM.…”
Section: Immunogenic Profile Of the Hostsupporting
confidence: 80%
“…Among HAM/TSP patients, FAS levels correlated positively with lymphocyte activation, but the increased lymphocyte FAS expression was linked to decreased apoptosis and increased lymphoproliferation in cell culture and a strong increase in cellular FAS expression upon HAM/TSP progression ( Menezes et al, 2017 ). Moreover, Rosado et al (2017) found an association between the FAS -670 AA genotype and the higher proviral load among HAM/TSP patients.…”
Section: Discussionmentioning
confidence: 89%
“…The search for host immunogenetic markers, possibly associated with HTLV-1 infection and progression to disease was pursued by our research group in the Amazon region of Brazil and other groups elsewhere ( Nishimura et al, 1991 ; Jeffery et al, 2000 ; Pontes et al, 2005 ; Alves et al, 2007 ; Vallinoto et al, 2012 , 2015 ; de Sá et al, 2016 ; Rosado et al, 2017 ). Polymorphisms rs1800450 (allele B, codon 54) and rs1800682 (-670A/G) located in MBL2 and FAS genes, respectively, were strongly associated with HTLV-1 infection.…”
Section: Introductionmentioning
confidence: 99%